PENGARUH GREEN ECONOMY TERHADAP PENINGKATAN PRODUKTIVITAS SEKTOR PERTANIAN LOKAL - Melyana R Pugu; Rita Hayati; Sigit Sugiardi; Al-Amin (JOURNAL OF COMMUNITY DEDICATION, 2025)
The purpose of this research is to see how the Influence of Green Economy on Increasing Productivity of the Local Agricultural Sector. The method of this research is This research is a type of literature research; This means that the information materials used come from library sources in the form of books, encyclopedias, magazines, journals, newspapers, journals, and others. The form of this research is descriptive, analytical, and critical. The application of the green economy concept in the local agricultural sector can have a positive impact on increasing productivity, especially with an approach that focuses on sustainability and wise management of natural resources. Through technological innovation, more efficient management of nature, and access to a wider range of markets, local farmers can increase their agricultural yields, reduce production costs, and improve socio-economic well-being. Therefore, the green economy is not only beneficial for environmental sustainability, but also provides better economic opportunities for the local agricultural sector.